Reflections on Health Workforce Development; Comment on "Health Professional Training and Capacity Strengthening Through International Academic Partnerships: The First Five Years of the Human Resources for Health Program in Rwanda" - Gilles Dussault (Kerman University of Medical Sciences, 2019)
This commentary addresses the statement that "the authors believe that the HRH [Human Resources for Health] Program can serve as a model for other initiatives that seek to address the shortage of qualified health professionals in low-income countries and strengthen the long-term capacity of local academic institutions." I adopt the position of the devil's advocate and ask whether a country, with a profile comparable to Rwanda's, should adopt this twinning model. I suggest that the alignment with population and other capacity development needs should be the main criteria of decision.